"Too Shocked to Search" The Covid-19 Shutdowns' Impact on the Search for Apprenticeships - Daniel Goller; Stefan C. Wolter (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This study is, to the best of our knowledge, the first analysis of apprenticeship supply that allows us to analyse the effects of the shutdowns triggered by the COVID-19 pandemic before, during and after these shutdowns by means of daily searches for vacant apprenticeships. Analysing over 10 million search queries on the national administrative platform for apprenticeship offers from February 2020 until April 2021 we find a sharp reduction of up to 40% in the daily number of search queries associated to the first shutdown in March 2020, followed by some catch-up effect thereafter. Although we find a strong relationship between the intensity of the politically imposed restrictions due to the COVID-19 pandemic and daily search queries, this relationship weakens over time as the pandemic progresses. Finally, we find a large heterogeneity of effects, but all regions and occupational groups studied show a statistically significant negative effect of the measures on the search intensity for apprenticeships.
Keywords: I20; J22; 330; Covid-19; Switzerland; stringency index; apprenticeship